Attualizzare Dante : prospettive di ricerca nei manuali di letteratura per la scuola italiana - Simone Marsi (Perspectives Médiévales)
The academic research on Dante Alighieri has recently focused its attention on the modernization of his works, analyzing, for example, the rewriting of Divine Comedy in pop culture (songs, comics, cinema, videogames, etc.). The aim of this article is to investigate the way in which Dante’s works are modernized in some popular Italian literature textbooks, to understand how his figure can be disseminated among generations of Italian students by a non-historical or non-chronological point of view.